The cost of the training and supervision of community health workers to improve exclusive breastfeeding amongst mothers in a cluster randomised controlled trial in South Africa - Gavin George; Takunda Mudzingwa; Christiane Horwood (BMC, 2020)
Abstract Background Interventions targeting community health workers (CHWs) aim to optimise the delivery of health services to underserved rural areas. Whilst interventions are evaluated against their objectives, there remains limited evidence on the economic costs of these interventions, and the practicality and value of scale up. The aim of this paper is to undertake a cost analysis on a CHW training and supervision intervention using exclusive breastfeeding rates amongst mothers as an outcome measure. Methods This is a retrospective cost analysis, from an implementer's perspective, of a cluster randomised controlled trial investigating the effectiveness of a continuous quality improvement (CQI) intervention aimed at CHWs providing care and support to pregnant women and women with babies aged < 1 year in South Africa. Results One of the outcomes of the RCT revealed that the prevalence of exclusive breastfeeding (EBF) significantly improved, with the cost per mother EBF in the control and intervention arm calculated at US$760,13 and US$1705,28 respectively. The cost per additional mother practicing EBF was calculated to be US$7647, 88, with the supervision component of the intervention constituting 64% of the trial costs. In addition, women served by the intervention CHWs were more likely to have received a CHW visit and had significantly better knowledge of childcare practices. Conclusion Whilst the cost of this intervention is high, adapted interventions could potentially offer an economical alternative for achieving selected maternal and child health (MCH) outcomes. The results of this study should inform future programmes aimed at providing adapted training and supervision to CHWs with the objective of improving community-level health outcomes.